Methodological Individualism - Bulle, Nathalie (Taylor & Francis, 2024)
Originating in the late 19th century and becoming the subject of ongoing methodological debates in the social sciences, methodological individualism is a paradigm that focuses on understanding social phenomena through the actions and choices of individuals rather than through collective explanations. This book highlights its theoretical bases as defined and developed in the writings of its founders and early proponents in the context of the liveliest methodological battles in the social sciences. It addresses fundamental epistemological issues, including the distinction between explanation in the social sciences and natural sciences, the rational bases for understanding social actions, the relation of social wholes to their parts, and the connections between social concepts and the phenomenal world. Bringing together new English translations of foundational texts by Carl Menger, Joseph Schumpeter, Georg Simmel, and Max Weber, this book provides key insights into one of the essential methodological paradigms in the social sciences, corrects misconceptions, and advances a deeper understanding of methodological individualism as a robust and valuable approach to explaining social phenomena. It will therefore appeal to scholars and students of sociology and sociological theory with an interest in questions of social science methodology.